The Psychoanalysis in The Hunger Games: The Ballad of Songbirds and Snakes - Elsye Stanicia Wijaya; Wahyu Budi (Journal of Literature Review, 2025)
This research explores the id, ego, and superego of the main character of the movie The Hunger Games: The Ballad of Songbirds & Snakes. The aim of this research is to explain about the id, ego, and superego of the main character’s acts. The researcher applies a qualitative study method, Freud's psychoanalysis approach, and Ekman's basic emotions to identify the main character’s id, ego, and superego. The researchers analyzed 11 data from the movie. There are 3 data for id, 5 for ego, and 3 for superego. Based on the research, the main character’s id is clearly a fight between his ambitions and moral uncertainty. The ego is revealed when the main character prioritizes his desires over the well-being of others. The superego manifests when he could keep the capitol’s authorities running smoothly and orderly. The researcher suggests that the readers could understand about their personal goals and how they connect with their beliefs through this research.